KARAKTERISASI PROTEASE BACILLUS SUBTILIS A1 INACC B398 YANG DIISOLASI DARI TERASI SAMARINDA - Soeka, Yati Sudaryati; Sulistiani, Sulistiani (Research Center for Biology-Indonesian Institute of Sciences, 2014)
Proteases is enzyme that breaks the peptide bond to produce amino acids and simpler peptides. This enzyme can be isolated from a variety of sources such as plants, animals and microbe. Alkaline proteases of microbial origin possess considerable industrial potential due to their biochemical diversity and wide applications in tannery, food, medicinal formulations and detergents. The objectives of the research was to determine the characteristics of the protease enzyme produced by strain A1, including incubation time, substrate concentration azokasein, the optimum temperature and pH also stability. The effect of some metal ions as activators or inhibitors of the protease enzyme activity measured with a spectrophotometer at ? 280 nm. Strain A1 was identified by using 16S rDNA sequencing and phylogenetic analysis based on Neighbor Joining method. Strain A1 protease activity was qualitatively demonstrated the presence of a clear zone around the colonies in the medium containing 1% skim milk. Result showed that the highest activity were incubation time of three days, temperature of 50 ºC and pH 8.5 were 87.35 U/mL, 83.44 U/mL and 93.11 U/mL, respectively. Effect of metal ions in the form of divalent and monovalent cations at a concentration of 1 mM on protease A1 activated by divalent cations CaCl2, MnCl2 while divalent cations CuCl2, HgCl2 and monovalent cations KCl, NaCl were inhibitors of each enzyme activity. Result from molecular identification based on 16S rDNA sequence and phylogenetic analysis using Neighbor Joining method suggested that strain A1 was Bacillus subtilis. The strain was registered in the InaCC collection (no. B 398).